Collaboration in construction supply chain in developing countries - Simões, Carolina Ponte Negraes (2020)
Highlights: Supply chain collaboration has been presented in recent decades as a solution to performance issues. However, collaborative supply chains are far from being a reality in the construction industry, especially in emerging countries. Rio de Janeiro, a state of Brazil, was used to investigate CSC (Construction Supply Chain) in an emerging country.Purpose: This article aims to evaluate the characteristics of CSC (Construction Supply Chain) collaboration and identify its critical elements. These elements were also compared in two groups of construction companies: small and medium/large construction companies, in order to verify whether size influences the degree of collaboration.Design / methodology / approach: This study used a combination of two methods: literature review and application of a survey to construction companies in the state of Rio de Janeiro. Data collection was performed from October 2018 to January 2019. The statistical analysis of the elements was performed using the software “R”, by Mann-Whitney U test.Findings: The survey revealed that the elements considered the most important for collaboration were: “joint planning and decision making”, “trust”, and “collaborative culture”. On the other hand, the element considered of minor importance for collaboration was “Information Sharing”. Comparison of the two groups of companies made it possible to conclude that there is a gap between the two groups of builders evaluated, and the medium/large builders were more prone to collaboration. Thus, the article suggests on which points effective collaboration in the CSC should be given attention.Research limitations / implications: This study was limited to researching collaboration in the CSC in construction companies located in the state of Rio de Janeiro.Originality / value: This article contributes to the literature on collaboration at CSC in Brazil and emerging countries, since there are few studies in this area for emerging countries.